Investigating the Long-Term Effects of Anthropogenic Practices on Soil Features (MAUSAM, 2024)
Anthropogenic practices have been increasingly conducted on the rise in addressing the escalatingdemands for socioeconomic development, resulting in significant impacts on land ecosystems. This research seeks toevaluate the influence of anthropogenic activities on soil features in mountainous regions of Vietnam by focusing 84samples collected from 12 locations across Lam River Basin at seven soil profiles (0-10, 10-20, 20-30, 30-40, 40-60, 60-80 and 80-100 cm).The findings reveal notable differences in soil texture among land use types (LUTs). Forest cover lands (FCLs),showed the least amount of sand content, varying from 29.7% to 37.6%, while unplanted and bare lands (UBLs) had thehighest sand ratios, up to 53.9%. FCLs exhibited lowest bulk density (BD), soil porosity (SP) and soil electricalconductivity (EC) and C:N ratio with respective ranges of 0.93-1.29 g.cm-3, 32.7-36.5%, 0.526-0.743 mS.m-1 and6.74 -8.52, respectively.In contrast, crop cultivation lands (CCLs) demonstrated higher values for BD (1.17-1.25 g/cm3), SP (39.25-43.19%), EC (0.583-0.792 mS.m-1) and C:N ratio (11.27-15.77). UBLs, on the other hand, exhibited even highest valuesup to 1.23-1.36 g.cm-1, 43.19-49.62%, 0.437-0.619 mS.m-1 and 11.68-16.58% and displayed high levels of exchange ironsand soil organic content compared to FCLs. Other factors such as pH varied little in space between the sampled soillocations and along the soil profiles. Overall, the study indicates that anthropogenic practices have impacts on the soilfeatures across the study area.